A W-Band backward-wave oscillator based on planar helix slow wave structure - Kumar, Ajith M. M. (2020)
A backward-wave oscillator (BWO) operating at W-band is presented. The BWO is based on a microfabrication-compatible planar helix slow wave structure with straight-edge connections (PH-SECs). The oscillator is designed to operate with a beam current of 20 mA and a beam voltage varying from 7 kV to 11 kV. Dispersion characteristics and their sensitivity to some of the geometrical parameters are presented. The particle-in-cell simulation results show that the oscillator frequency tunes from 86.9 GHz to 100.07 GHz with a tunable bandwidth of 14%. The oscillator provides a maximum peak output power of 2.3 W and a peak efficiency of 1.62%. Results of oscillator performance with a beam current of 18 mA and 16 mA are also presented. To validate the simulation results of the PH-SEC, a scaled version of the PH-SEC operating at X-band is fabricated. The measured S-parameters and the phase velocity for the fabricated structure match very well with the simulation results.